On the efficacy of anthracene isomers for triplet transmission from CdSe nanocrystals - Xia, Pan (2017)
The effect of isomeric substitutions on the transmitter for triplet energy transfer (TET) between nanocrystal (NC) donor and molecular acceptor is investigated. Each isomeric acceptor is expected to bind in a unique orientation with respect to the NC donor. We see that this orbital overlap drastically affects the transmission of triplets. Here, two functional groups, the carboxylic acid and dithiocarbamate, were varied between the 1-, 2- and 9-positions of the anthracene ring to give three ACA and three ADTC isomers. These six anthracene isomers served as transmitters for triplets between CdSe NC sensitizers and 9,10-diphenylanthracene annihilators for photon upconversion. The photon upconversion quantum yield (QY) is the highest for 9-ACA (12%), lowest for 9-ADTC (0.1%), around 3% for both 1-ACA and 1-ADTC, and about 1% for the 2-isomers. These trends in QYs are reflected in the rates of TET given by ultrafast transient absorption spectroscopy where a maximum of 3.8 × 107 s−1 for 9-ACA was measured. Molecular excited state energy levels were measured both in solution and polymer hosts to correlate structure to TET. This work confirms that anthracene excited states levels are very sensitive to molecular substitution, which in combination with orbital overlap, critically affect Dexter-based TET.